2019
DOI: 10.1016/j.jallcom.2018.11.263
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thermal stability of 2D and 3D CoAl2O4 particles in core-shell nanostructures by Raman spectroscopy

Abstract: We are studying the formation of a nanostructured spinel CoAl2O4 layer on α-Al2O3 giving rise to a core-shell composite. In the final product, two mechanisms of CoAl2O4 crystallization onto a α-Al2O3 microparticle surface are observed, depending on the dispersion grade of Co3O4: a 3D nanostructure from the arrangement of Co3O4 agglomerated nanoparticles; 2D nanoparticles from the diffusion mechanism of isolated Co3O4 nanoparticles. As a consequence, two different crystallization pathways may occur during the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…The wavenumbers of the Raman active peaks are obtained via fitting the spectra using a Lorentz function, and the results are consistent with the previous works [ 25 27 ]. The F 2 g (1) mode at 202 cm −1 is assigned to the Co/Al-O 4 tetrahedron translation [ 25 ]. The position of E g mode is reported to have a reasonable correlation with the cation radius at the 8a site [ 11 ].…”
Section: Resultssupporting
confidence: 88%
“…The wavenumbers of the Raman active peaks are obtained via fitting the spectra using a Lorentz function, and the results are consistent with the previous works [ 25 27 ]. The F 2 g (1) mode at 202 cm −1 is assigned to the Co/Al-O 4 tetrahedron translation [ 25 ]. The position of E g mode is reported to have a reasonable correlation with the cation radius at the 8a site [ 11 ].…”
Section: Resultssupporting
confidence: 88%
“…CoAl2O4 crystallizations are envisaged on the α-Al2O3 microparticles surface (Figure 2b). These nanocrystals have an irregular shape, with an average equivalent diameter of 427±118 nm, and present a hole in the middle; they expose the lowest-energy (111) facets represented in Figure S1c [20,25]. The morphology of the CoAl2O4 powder before and after ball milling is shown in Figure 2c-f.…”
Section: Textural and Structural Characterizationmentioning
confidence: 99%
“…Such conclusions were drawn from the results of XRD studies ( Figure S1). XPS analyses of the fresh and used samples revealed traces of zirconia contamination, attributed to the milling procedure [55], and indicated that all the samples had a normal spinel structure and Co 2+ cations in tetrahedral sites ( Figure S2, Table S1) [56,57]. Figure S3a shows a STEM-HAADF (Scanning Transmission Electron Microscopy-High Angle Annular Dark Field) illustrative image of a region with bright spots dispersed all over the CoAl 2 O 4 that correspond to Pt and Ni, according to the EDX mapping of these elements in the region.…”
Section: Textural and Structural Characterizationmentioning
confidence: 99%